Scientific protocols for forensic examination of clothing - Taupin, Jane Moira (Protocols in forensic science series, 2011)
From the Publisher: When a crime or other incident takes place, clothing items are often present or left behind, and can become directly involved in the case itself. Items of clothing are thus one of the most common types of exhibit examined in court. They can provide valuable information in cases of violent crimes, such as homicide or rape, as well as in burglary, robbery, arson, and vehicular accidents. A unique reference in the forensic arena, The first of its kind, Scientific Protocols for Forensic Examination of Clothing discusses the forensic examination of clothing in criminal cases. It examines the ramifications of DNA profiling and its effect on the screening approach to clothing examination. Coverage includes protocols and procedures, preliminary assessment, examination, testing and sampling, quality assurance and control, and the significance of results.